Martyrs and Living Martyrs of the People’s War in Nepal - Marie Lecomte-Tilouine (South Asia Multidisciplinary Academic Journal)
In Nepal, the Maoists’ armed wing (PLA) developed as a collective of martyrs-to-be, whose example was disseminated as soon as they fell through tributes, poems and ceremonies. Its dynamic relied on self-sacrifice rather than any heroic prowess, and acquired a strong power of attraction in that it fundamentally asserts that anyone, whether illiterate, poor or of the lowest status, is of ‘priceless’ value, and can contribute to the project to change the order of things by putting their lives at stake. The People’s War also brought about a wave of ‘Living Martyrs’, who survived the war and who are now busy recording their past experiences. They combine all the ingredients in terms of pathos and achievement to become historical figures and models for the future, while fallen immortals have already lost their individualities and play a collective and anonymous role.